A Comparative analysis of the translation of harf fi in surah Ali' Imran By Talal itani and Muhammad Marmaduke Pickthall - Rilla Fadhilatul Mufidah (Fak. Adab dan Ilmu Budaya UIN Sunan Kalijaga, 2019)
etik,1./ws.c.1